2012
DOI: 10.1007/s00277-012-1474-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein Z polymorphisms associated with vaso-occlusive crisis in young sickle cell disease patients

Abstract: We investigated the association of protein Z (PZ) promoter (rs3024718, rs3024719, and rs3024731) and intron (rs3024735; G79A) SNPs with sickle cell disease (SCD) vaso-occlusive crisis (VOC). Study subjects included 239 SCD patients with VOC and 138 pain-free SCD control patients. PZ genotyping was done by allelic discrimination (real-time PCR) assays. The minor allele frequency of rs3024718 (P=0.03), rs3024719 (P=0.02), rs3024731 (P<0.001), and rs3024735 (P<0.001) were higher in VOC patients than control SCD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…(48,49). Variability in the genes encoding for receptors, enzymes, or transporter channels such as GTP cyclohydroxylase, COMT, TRPV1, and KCNS1 has been implicated in non-SCD painful conditions (50)(51)(52)(53)(54)(55); some of which have been examined in SCD pain (35,(56)(57)(58)(59)(60).…”
Section: Lessons From Non-scd Pain Conditions and Future Directionsmentioning
confidence: 99%
“…(48,49). Variability in the genes encoding for receptors, enzymes, or transporter channels such as GTP cyclohydroxylase, COMT, TRPV1, and KCNS1 has been implicated in non-SCD painful conditions (50)(51)(52)(53)(54)(55); some of which have been examined in SCD pain (35,(56)(57)(58)(59)(60).…”
Section: Lessons From Non-scd Pain Conditions and Future Directionsmentioning
confidence: 99%
“…Very few investigators ( n = 4) reported performing a power analysis, revealing majority of these studies were exploratory in nature ( n = 18). Of those, three of the four studies reported sufficient power (79%–84%) to detect associations between SNPs of interest and an SCD-related pain phenotype ( 13 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the sample size of our study, or the unreported attacks of VOC missed by the patients or their caregivers. The study of Mahdi and colleagues 25 reported that the polymorphic genotypes were significantly higher in SCD patients with VOC, and this SNP could be considered as molecular risk factor for vaso-occlusion.…”
Section: Discussionmentioning
confidence: 96%
“…These frequencies go with that previously reported in Bahraini patients being 65%, 29%, and 5% for the GG, GA, and AA genotypes, respectively. 25 SCD complications may be modified by genetic and acquired risk factors for vasculopathy and several studies have reported that Proein Z G79A polymorphism is associated with thrombotic complications.…”
Section: Discussionmentioning
confidence: 99%